Analisis Manajemen Pengembangan Minat dan Bakat Masuk Perguruan Tinggi Favorit (Studi Kasus SMA Tamansiswa Pematangsiantar) - Siti Charunnisa Sinaga (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study was to analyze the management of the development of interests and talents of SMA Tamansiswa Pematangsiantar students. Implementation is based on grouping students' learning achievement abilities. After the implementation is carried out, supervision is carried out by monitoring every field carried out by the teacher who is appointed as an extracurricular coordinator and the development of students is carried out during the activity. There is a significant impact on the achievement of the objectives of the program by paying attention to good planning, implementation and supervision. The research method used is a qualitative research method. By using the type of case study research that is telling and describing the real findings found by the researcher. The results obtained by the researchers in the form of school profiles, school history, and findings obtained through observation in the form of facts, documentation, interviews, and document data.